Influence of Sex and Previous Concussion History on Postconcussive Recovery in Young Athletes. (March 2020) - Chand, Manisha R.; Kanwar, Sumit; Calvo, Cecilia; Peck, Evan
Abstract : Objective: To determine whether concussed female athletes with a previous history of concussion have longer postconcussive recovery than that of male counterparts. Design: Retrospective cohort study. Setting: Outpatient sports medicine clinic in an academic practice. Participants: Male and female youth, high school, and collegiate athletes (n = 431; ages = 10-21 years) who sustained a sport-related concussion (SRC). Interventions: The clinical courses of young athletes treated for concussion by 1 provider at an outpatient sports medicine clinic were retrospectively reviewed. Main Outcome Measures: Recovery time was compared after an SRC with relationship to sex and previous concussion history. Results: When comparing male and female athletes with a previous history of concussion, there were no differences found ( P = 0.820) in SRC recovery time. Regardless of previous concussion history, males recovered faster from an SRC compared with their female counterparts ( P = 0.0002). Without regard to sex, those with no previous history of concussion recovered faster than those with a previous concussion history, although the difference was not statistically significant ( P = 0.668). Athletes with a previous history of concussion were more likely to require neuropsychology referral than those with no previous concussion history ( P = 0.021), and females, without regard to concussion history, were more likely to require neuropsychology referral than males ( P = 0.001). Conclusions: A previous concussion history does not appear to significantly influence postconcussive recovery time in young athletes, although it does increase the probability of neuropsychological referral. Without regard to a previous concussion history, young female athletes recover slower than males from concussion and are also more likely to require neuropsychological referral.